Combined review of the existing maximum residue levels (MRLs) for the active substances metalaxyl and metalaxyl‐M - European Food Safety Authority (EFSA) (EFSA Journal, 2015)
Abstract In compliance with Article 43 of Regulation (EC) No 396/2005, the European Food Safety Authority (EFSA) received from the European Commission (EC) a mandate to update its previous review of the maximum residue levels (MRL) for metalaxyl, taking into account new information provided in the Renewal Assessment Report for metalaxyl‐M and taking into account previous MRL assessments for metalaxyl‐M. EFSA is providing a reasoned opinion combining the MRL reviews of metalaxyl and metalaxyl‐M and taking into consideration the additional data. Based on the assessment of the available data, one set of MRL proposals was derived for metalaxyl and metalaxyl‐M (using the OECD calculator) and a consumer risk assessment was carried out. Although no apparent risk to consumers was identified, some information required by the regulatory framework was found to be missing. Hence, the consumer risk assessment is considered indicative only and some MRL proposals derived by EFSA require further consideration by risk managers.